PRIORITISING THE PRACTICES THAT INFLUENCE THE OPERATIONAL PERFORMANCE OF MANUFACTURING ORGANISATIONS USING HYBRID AHP-TOPSIS ANALYSIS - Arshad, Asif; Mahmood, Asif; Salam, Abdus (The South African Journal of Industrial Engineering, 2020)
Organisations cannot put their efforts equally into all the best practices that impact operational performance, due to their limited resources, their ineffective usage, government policies, and inadequate strategic planning. In this contribution, we aim to identify and prioritise the practices with the most impact on operational performance. Twelve practices that steer operational performance were identified through a literature survey. Second, the identified practices were prioritised and evaluated, based on improving operational performance by using a hybrid approach. The analytical hierarchy process (AHP) and the technique for order performance by similarity to ideal solution (TOPSIS) method were used such that AHP was applied to determine the relative weights of alternatives, and then the final ranking was obtained by conducting a TOPSIS analysis. Empirical data were collected from eight experts and 417 users at operational-level. The results suggest that lean management, total quality management, six sigma, and supply chain management practices rank 1st, 2nd, 3rd, and 4th respectively, signifying the practices with the most influence and making the greatest contribution. This strategic understanding will help researchers and practitioners to frame competitive strategies in order to pay more attention to those practices that have a greater influence on operational performance.